Manufacturing method of lithium-ion secondary battery

JP7633964B2Active Publication Date: 2025-02-20PRIME PLANET ENERGY & SOLUTIONS INC
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
JP2022085955
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2022-05-26
Publication Date
2025-02-20
Estimated Expiration
2042-05-26

Smart Images

  • Figure 0007633964000002
    Figure 0007633964000002
  • Figure 0007633964000003
    Figure 0007633964000003
  • Figure 0007633964000004
    Figure 0007633964000004
Patent Text Reader

Abstract

To provide a method for manufacturing a lithium ion secondary battery, by which "Al elution from the surface of a positive electrode current collector foil during high-load energization in an early stage of use" can be reduced.SOLUTION: A method for manufacturing a lithium ion secondary battery comprises: a positive electrode paste-producing step S1 of mixing positive electrode active material particles 64 and a solvent 69 to produce a positive electrode paste 63P; a positive electrode plate-producing step S2 of applying the positive electrode paste 63P to a surface 61b, 61c of positive electrode current collector foil 61, and drying it, to produce a positive electrode plate 60; an electrode body-producing step S3 of producing an electrode body 50 having the positive electrode plate 60 and a negative electrode plate 70; a housing step S4 of housing the electrode body 50 in a battery case 30; a liquid-charging step S5 of charging a nonaqueous electrolyte 90 into the battery case 30 with the electrode body 50 housed therein to produce a liquid-charged battery 1B; and an initial charging step S6 of initially charging the liquid-charged battery 1B. In the positive electrode paste-producing step S1, a positive electrode paste 63P with hydroxide particles 67 further mixed therein is produced.SELECTED DRAWING: Figure 3
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a method for producing a lithium ion secondary battery. [Background technology]

[0002] Patent Document 1 discloses a method for producing a lithium ion secondary battery having a positive electrode plate having a positive electrode active material layer on the surface of a positive electrode current collector foil made of aluminum foil, a negative electrode plate, and a nonaqueous electrolyte solution containing LiPF6. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2018-60689 A Summary of the Invention [Problem to be solved by the invention]

[0004] In a lithium-ion secondary battery having a positive electrode plate having a positive electrode active material layer on the surface of a positive electrode current collector foil made of aluminum foil, a negative electrode plate, and a non-aqueous electrolyte containing LiPF6, when a current with a large load such as rapid charging is applied, a high potential may occur locally on the positive electrode current collector foil. Then, when the local area with the high potential corrodes, Al (aluminum) dissolves from the surface of the local area, and this accumulates on the surface of the negative electrode, which may cause an internal short circuit. Specifically, in a lithium-ion secondary battery in the early stages of use, a coating of AlF3 having high corrosion resistance is not sufficiently formed on the surface of the positive electrode current collector foil, so that dissolution of Al may occur due to the above-mentioned corrosion.

[0005] In contrast, in the lithium ion secondary battery of Patent Document 1, LiBF4 and LiFOB are added to the non-aqueous electrolyte as additives that promote the formation of an AlF3 coating on the surface of the positive electrode current collector foil. However, these additives are expensive, and since the formation of the AlF3 coating is insufficient in the initial stage of use, there is a risk of Al elution due to corrosion when a high load current is applied, such as during rapid charging.

[0006] The present invention has been made in consideration of the above-mentioned current situation, and aims to provide a method for manufacturing a lithium-ion secondary battery that can reduce "elution of Al from the surface of a positive electrode current collector foil when a high load current is applied in the early stages of use." [Means for solving the problem]

[0007] (1) One aspect of the present invention relates to a method for producing a lithium ion secondary battery including a positive electrode plate having a positive electrode active material layer on a surface of a positive electrode current collector foil made of aluminum foil, a negative electrode plate, a non-aqueous electrolyte solution containing LiPF6, and a battery case that houses them, the method including: a positive electrode paste preparation step of mixing positive electrode active material particles and a solvent to prepare a positive electrode paste; a positive electrode plate preparation step of applying the positive electrode paste to the surface of the positive electrode current collector foil and drying the applied positive electrode paste to prepare the positive electrode plate having the positive electrode active material layer on the surface of the positive electrode current collector foil; an electrode body preparation step of preparing an electrode body having the positive electrode plate and the negative electrode plate; an accommodation step of accommodating the electrode body inside the battery case; a liquid injection step of injecting the non-aqueous electrolyte solution into the battery case that accommodates the electrode body to prepare a liquid injection-completed battery; and an initial charging step of initially charging the liquid injection-completed battery, wherein the positive electrode paste preparation step further includes LiOH particles The positive electrode paste is prepared by mixing the above, and the above is selected from the solid content of the positive electrode paste. LiOH particles The above-mentioned ratio of solids excluding LiOH particles The mixing ratio of the above is within the range of more than 2.0 wt % and less than 5.0 wt %.

[0008] In the above-mentioned method for manufacturing a lithium ion secondary battery, in the positive electrode paste preparation step, hydroxide particles are further mixed in addition to the positive electrode active material particles and the solvent to prepare a positive electrode paste containing hydroxide particles. Then, in the positive electrode plate preparation step, the positive electrode paste containing hydroxide particles is applied to the surface of a positive electrode current collector foil, and the applied positive electrode paste is dried to prepare a positive electrode plate having a positive electrode active material layer containing hydroxide particles on the surface of the positive electrode current collector foil. Then, a lithium ion secondary battery is manufactured using this positive electrode plate.

[0009] By manufacturing a lithium ion secondary battery using such a positive plate, a coating of AlF3 having high corrosion resistance is more easily formed on the surface of the positive current collector foil during the manufacturing process of the battery than in the past. Specifically, during the period from when a nonaqueous electrolyte is injected into a battery case containing the positive plate and the like until the battery is completed and ready to be shipped, the coating formation reaction of AlF3 on the surface of the positive current collector foil is promoted more than in the past. In particular, during the initial charging process, the coating formation reaction of AlF3 is promoted. Therefore, the lithium ion secondary battery manufactured as described above has a higher corrosion resistance on the surface of the positive current collector foil when it is completed and ready to be shipped than in the conventional lithium ion secondary battery. Therefore, in the lithium ion secondary battery manufactured by the above manufacturing method, "Al elution from the surface of the positive current collector foil when a high load current is applied in the early stages of use" is reduced compared to the conventional lithium ion secondary battery.

[0010] When LiOH particles are used as hydroxide particles to be added to the positive electrode paste, a highly corrosion-resistant AlF3 coating is formed on the surface of the positive electrode current collector foil (aluminum foil) through the series of reactions (a) to (c) below. The surface of the positive electrode current collector foil (aluminum foil) used in the positive electrode plate manufacturing process is covered with an Al2O3 coating, which is an oxide coating.

[0011] (a) LiOH in the positive electrode active material layer decomposes to generate HO. 2LiOH → Li2O + H2O (Eq. 1) (b) The generated H2O reacts with LiPF6 in the non-aqueous electrolyte to produce HF. LiPF6+H2O→LiF+POF3+2HF (Formula 2) (c) The generated HF reacts with the Al2O3 coating on the surface of the positive current collector foil, producing an AlF3 coating on the surface of the positive current collector foil. Al2O3+6HF→2AlF3+3H2O (Formula 3)

[0012] Even when hydroxide particles other than LiOH particles are used as the hydroxide particles added to the positive electrode paste, the hydroxide particles decompose in the positive electrode active material layer to generate H2O, which causes the reactions of formulas 2 and 3 above, producing an AlF3 coating on the surface of the positive electrode current collector foil.

[0013] (2) Furthermore, in the method for producing a lithium ion secondary battery according to (1) above, the hydroxide particles may be LiOH particles.

[0014] By using LiOH particles as hydroxide particles mixed in the positive electrode paste, as described above, a coating of AlF3 is formed on the surface of the positive electrode current collector foil during the manufacturing process of the battery. Therefore, even if a high load current is applied in the early stage of use of the battery, the occurrence of Al elution from the surface of the positive electrode current collector foil can be reduced. In addition, the decomposition of LiOH in the positive electrode active material layer produces Li, which is useful for lithium ion secondary batteries, which is preferable.

[0016] Of the solid content of the positive electrode paste LiOH particles For solids excluding LiOH particles By making the mixing ratio of more than 2.0 wt%, it becomes easier for an AlF3 coating to be formed on the surface of the positive electrode current collector foil, and it is possible to prevent the occurrence of Al elution from the surface of the positive electrode current collector foil. LiOH particles If the mixing ratio is 5.0 wt% or more, the discharge capacity of the battery will decrease significantly. LiOH particles For solids excluding LiOH particlesThe mixing ratio of is preferably within the range of more than 2.0 wt % and less than 5.0 wt %. The solid content of the positive electrode paste is the components of the positive electrode paste other than the solvent. [Brief description of the drawings]

[0017] [Figure 1] 1 is a plan view (top view) of a lithium ion secondary battery according to an embodiment. [Diagram 2] FIG. 2 is a front view of the lithium-ion secondary battery. [Diagram 3] 4 is a flowchart showing a procedure for manufacturing the lithium ion secondary battery. [Figure 4] 4A to 4C are diagrams illustrating a method for manufacturing the lithium ion secondary battery. [Diagram 5] 4A to 4C are other diagrams illustrating the method for manufacturing the lithium ion secondary battery. [Figure 6] FIG. 2 is a cross-sectional view of a positive electrode plate of the lithium-ion secondary battery. [Figure 7] FIG. 2 is a cross-sectional view of a negative electrode plate of the lithium-ion secondary battery. [Figure 8] FIG. 2 is a perspective view of an electrode body of the lithium ion secondary battery. [Figure 9] 4A to 4C are other diagrams illustrating the method for manufacturing the lithium ion secondary battery. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0018] Next, an embodiment of the present invention will be described. The lithium ion secondary battery 1 of this embodiment includes a battery case 30, an electrode assembly 50 housed inside the battery case 30, a positive electrode terminal member 41, and a negative electrode terminal member 45 (see Figs. 1 and 2). The battery case 30 is a hard case made of metal, and has a rectangular box shape. The battery case 30 includes a metallic case body 21 having a square, bottomed cylindrical shape, and a metallic lid body 11 having a rectangular, flat plate shape that closes the opening of the case body 21 (see Figs. 1 and 2).

[0019] Two rectangular cylindrical through holes (a first through hole and a second through hole, not shown) are formed in the lid body 11. A positive electrode terminal member 41 is inserted into the first through hole, and a negative electrode terminal member 45 is inserted into the second through hole (see FIGS. 1 and 2). Note that cylindrical insulating members (not shown) are interposed between the inner peripheral surface of the first through hole of the lid body 11 and the outer peripheral surface of the positive electrode terminal member 41, and between the inner peripheral surface of the second through hole of the lid body 11 and the outer peripheral surface of the negative electrode terminal member 45.

[0020] The electrode body 50 has a positive electrode plate 60, a negative electrode plate 70, and a separator 80 interposed between the positive electrode plate 60 and the negative electrode plate 70. More specifically, the electrode body 50 is a wound electrode body including a strip-shaped positive electrode plate 60, a strip-shaped negative electrode plate 70, and a strip-shaped separator 80, and the positive electrode plate 60 and the negative electrode plate 70 are wound in a manner in which the separator 80 is interposed between them (see FIG. 8). The electrode body 50 contains a nonaqueous electrolyte 90 (see FIG. 2). The nonaqueous electrolyte 90 is also accommodated on the bottom side inside the battery case 30. The positive electrode plate 60 of the electrode body 50 is connected to a positive electrode terminal member 41 inside the battery case 30. The negative electrode plate 70 is connected to a negative electrode terminal member 45 inside the battery case 30.

[0021] The positive electrode plate 60 has a positive electrode current collector foil 61 made of aluminum foil, and a positive electrode active material layer 63 laminated on the surfaces (first surface 61b and second surface 61c) of the positive electrode current collector foil 61 (see FIG. 6). The positive electrode active material layer 63 contains positive electrode active material particles 64, a binder 65, a conductive material 66, and hydroxide particles 67. In this embodiment, the positive electrode active material particles 64 are lithium transition metal composite oxide particles, specifically Li(Ni 1 / 3 Mn 1 / 3 Co 1 / 3 )O2 particles are used. PVDF is used as the binder 65. Acetylene black is used as the conductive material 66. LiOH particles are used as the hydroxide particles 67.

[0022] The negative electrode plate 70 has a negative electrode current collector foil 71 made of copper foil, and a negative electrode active material layer 73 laminated on the surfaces (first surface 71b and second surface 71c) of the negative electrode current collector foil 71 (see FIG. 7). The negative electrode active material layer 73 contains negative electrode active material particles 74 and a binder 75. In this embodiment, graphite particles are used as the negative electrode active material particles 74. Also, CMC (carboxymethyl cellulose) and SBR (styrene butadiene rubber) are used as the binder 75.

[0023] The separator 80 has a porous resin sheet made of polyolefin and a heat-resistant layer made of heat-resistant particles formed on the surface of the porous resin sheet. In this embodiment, a three-layer structure porous resin sheet in which a porous polyethylene layer is interposed between two porous polypropylene layers is used as the porous resin sheet. The nonaqueous electrolyte 90 contains an organic solvent (specifically, ethylene carbonate, ethyl methyl carbonate, and dimethyl carbonate) and LiPF6.

[0024] Next, a method for manufacturing the lithium ion secondary battery 1 according to the embodiment will be described. Fig. 3 is a flowchart showing the flow of the method for manufacturing the lithium ion secondary battery 1. First, in step S1 (positive electrode paste preparation step), a positive electrode paste 63P is prepared. Specifically, positive electrode active material particles 64, binder 65, conductive material 66, hydroxide particles 67, and solvent 69 are mixed to prepare positive electrode paste 63P (see Fig. 4). Among the components of positive electrode paste 63P, the positive electrode active material particles 64, binder 65, conductive material 66, and hydroxide particles 67 are solid contents.

[0025] In the positive electrode paste preparation process of this embodiment, the mixing ratio of the hydroxide particles 67 to the solid content of the positive electrode paste 63P excluding the hydroxide particles 67 (specifically, the positive electrode active material particles 64, the binder 65, and the conductive material 66) is set to a range of 0.5 wt% or more and less than 5.0 wt%. That is, in the positive electrode paste 63P of this embodiment, the weight ratio of the hydroxide particles 67 to the solid content of the positive electrode paste 63P excluding the hydroxide particles 67 (specifically, the positive electrode active material particles 64, the binder 65, and the conductive material 66) is set to a range of 0.5 wt% or more and less than 5.0 wt%. In other words, when the weight ratio of the solid content of the positive electrode paste 63P excluding the hydroxide particles 67 (specifically, the positive electrode active material particles 64, the binder 65, and the conductive material 66) to the hydroxide particles 67 is set to 100:x, the relationship of 0.5≦x<5.0 is satisfied. The solid content of positive electrode paste 63P is the components of positive electrode paste 63P excluding solvent 69.

[0026] In this embodiment, the positive electrode active material particles 64 are lithium transition metal composite oxide particles, specifically, Li(Ni 1 / 3 Mn 1 / 3 Co 1 / 3 )O2 particles are used. PVDF is used as the binder 65. Acetylene black is used as the conductive material 66. LiOH particles are used as the hydroxide particles 67.

[0027] Next, in step S2 (positive electrode plate preparation step), the positive electrode paste 63P is applied to the first surface 61b of the band-shaped positive electrode current collector foil 61. As a result, a positive electrode paste layer made of the positive electrode paste 63P is formed on the first surface 61b of the positive electrode current collector foil 61. Next, the positive electrode paste 63P (specifically, the positive electrode paste layer made of the positive electrode paste 63P) applied to the first surface 61b of the positive electrode current collector foil 61 is dried. As a result, the solvent 69 evaporates from the positive electrode paste layer made of the positive electrode paste 63P, and the positive electrode active material layer 63 is formed on the first surface 61b of the positive electrode current collector foil 61 (see FIG. 5). In a similar manner, the positive electrode active material layer 63 is also formed on the second surface 61c of the positive electrode current collector foil 61 to prepare a band-shaped positive electrode plate 60 (see FIG. 6). The first surface 61b and the second surface 61c of the positive electrode current collector foil 61 (aluminum foil) provided to step S2 (positive electrode plate fabrication step) are covered with an Al2O3 coating, which is an oxide coating.

[0028] Thereafter, in step S3 (electrode body fabrication step), an electrode body 50 is fabricated having a strip-shaped positive electrode plate 60, a strip-shaped negative electrode plate 70, and a strip-shaped separator 80 interposed between the positive electrode plate 60 and the negative electrode plate 70. Specifically, the positive electrode plate 60, the negative electrode plate 70, and the separator 80 are wound in a manner such that the separator 80 is interposed between the positive electrode plate 60 and the negative electrode plate 70, to fabricate the electrode body 50, which is a wound electrode body (see FIG. 8).

[0029] Next, in step S4 (accommodating step), the electrode body 50 is accommodated inside the battery case 30. Specifically, first, the lid body 11 is prepared, and the positive electrode terminal member 41 and the negative electrode terminal member 45 are assembled to the lid body 11. Thereafter, the positive electrode terminal member 41 assembled to the lid body 11 and the positive electrode plate 60 included in the electrode body 50 are connected. Specifically, the positive electrode terminal member 41 and the positive electrode plate 60 included in the electrode body 50 are welded. Furthermore, the negative electrode terminal member 45 assembled to the lid body 11 and the negative electrode plate 70 included in the electrode body 50 are connected. Specifically, the negative electrode terminal member 45 and the negative electrode plate 70 included in the electrode body 50 are welded. As a result, the lid body 11 and the electrode body 50 are integrated via the positive electrode terminal member 41 and the negative electrode terminal member 45.

[0030] Next, the electrode body 50 integrated with the lid body 11 is housed inside the case body 21, and the opening of the case body 21 is closed by the lid body 11. In this state, the lid body 11 and the case body 21 are welded all around. As a result, the case body 21 and the lid body 11 are joined to form a battery case 30, and a completely assembled battery 1A is produced (see FIG. 9). The completely assembled battery 1A is a structure in which the battery case 30, the electrode body 50, the positive electrode terminal member 41, and the negative electrode terminal member 45 are assembled. Specifically, the completely assembled battery 1A includes the battery case 30, the electrode body 50 housed inside the battery case 30, and the positive electrode terminal member 41 and the negative electrode terminal member 45 connected to the electrode body 50.

[0031] Next, in step S5 (injection step), the nonaqueous electrolyte 90 is injected into the battery case 30 housing the electrode assembly 50 to produce a completely injected battery 1B (see FIG. 9). Specifically, an injection hole (not shown) is formed in the lid 11 of the battery case 30 constituting the completely assembled battery 1A. The nonaqueous electrolyte 90 is injected into the battery case 30 constituting the completely assembled battery 1A through this injection hole. This causes the electrode assembly 50 to be impregnated with the nonaqueous electrolyte 90, and causes the nonaqueous electrolyte 90 to be housed on the bottom side of the inside of the battery case 30. The injection hole is then sealed to produce a completely injected battery 1B.

[0032] Next, in step S6 (initial charging step), initial charging is performed on the battery 1B after injection is complete. This activates the battery 1B and turns it into a lithium ion secondary battery 1. In the initial charging step of this embodiment, the battery 1B after injection is CC charged at a constant current value of 0.2 C until the battery voltage value of the battery 1B reaches 4.1 V. After that, the lithium ion secondary battery 1 after initial charging is inspected, and the lithium ion secondary battery 1 is completed and ready for shipment.

[0033] In the past, in a lithium-ion secondary battery having a positive electrode plate having a positive electrode active material layer on the surface of a positive electrode current collector foil made of aluminum foil, a negative electrode plate, and a non-aqueous electrolyte containing LiPF6, when a high load current such as quick charging was applied, a high potential was sometimes generated locally on the positive electrode current collector foil. Then, when the local area with the high potential corrodes, Al (aluminum) is dissolved from the surface of the local area, and this is deposited on the surface of the negative electrode, which may cause an internal short circuit. Specifically, in a lithium-ion secondary battery in the early stages of use, a coating of AlF3 having high corrosion resistance is not sufficiently formed on the surface of the positive electrode current collector foil, so that the above-mentioned corrosion may cause Al to be dissolved.

[0034] In contrast, in this embodiment, as described above, in the positive electrode paste preparation step (step S1), a positive electrode paste 63P containing hydroxide particles 67 (specifically, LiOH particles) is prepared. Then, in the positive electrode plate preparation step (step S2), the positive electrode paste 63P containing the hydroxide particles 67 is applied to the first surface 61b and the second surface 61c of the positive electrode current collector foil 61 to prepare a positive electrode plate 60 having a positive electrode active material layer 63 containing the hydroxide particles 67 on the first surface 61b and the second surface 61c of the positive electrode current collector foil 61. Then, the lithium ion secondary battery 1 is manufactured using this positive electrode plate 60.

[0035] By manufacturing the lithium ion secondary battery 1 using such a positive electrode plate 60, a highly corrosion-resistant AlF3 coating is easily formed on the first surface 61b and the second surface 61c of the positive electrode current collector foil 61 during the manufacturing process of the battery 1. Specifically, the following series of reactions (a) to (c) occur from the time when the nonaqueous electrolyte 90 is poured into the battery case 30 containing the positive electrode plate 60 and the like until the battery 1 is ready for shipment, and thus the formation of the AlF3 coating is promoted on the first surface 61b and the second surface 61c of the positive electrode current collector foil 61 compared to the conventional method. In particular, the following series of reactions (a) to (c) are promoted during the initial charging step, and thus the formation of the AlF3 coating is promoted. The first surface 61b and the second surface 61c of the positive electrode current collector foil 61 (aluminum foil) provided for the positive electrode plate manufacturing step (step S2) are formed of an Al2O3 coating, which is an oxide coating.

[0036] (a) LiOH contained in the positive electrode active material layer 63 decomposes to generate H2O. 2LiOH → Li2O + H2O (Eq. 1) (b) The generated H2O reacts with LiPF6 contained in the non-aqueous electrolyte 90 to generate HF. LiPF6+H2O→LiF+POF3+2HF (Formula 2) (c) The generated HF reacts with the Al2O3 coating forming the first surface 61b and the second surface 61c of the positive current collector foil 61, generating an AlF3 coating on the first surface 61b and the second surface 61c of the positive current collector foil 61. Al2O3+6HF→2AlF3+3H2O (Formula 3)

[0037] Therefore, the lithium ion secondary battery 1 manufactured as described above has higher corrosion resistance of the first surface 61b and the second surface 61c of the positive electrode current collector foil 61 when completed and ready for shipment, compared to conventional lithium ion secondary batteries. Therefore, in the lithium ion secondary battery 1 manufactured by the manufacturing method of this embodiment, "elution of Al from the first surface 61b and the second surface 61c of the positive electrode current collector foil 61 when a high load current is applied in the early stages of use" is reduced, compared to conventional lithium ion secondary batteries.

[0038] <Examples 1 to 5> In Examples 1 to 5, in step S1 (positive electrode paste preparation step), the positive electrode paste 63P was prepared by varying the mixing ratio (wt%) of the hydroxide particles 67 to the solid content excluding the hydroxide particles 67 (specifically, the positive electrode active material particles 64, the binder 65, and the conductive material 66) of the solid content of the positive electrode paste 63P. That is, in Examples 1 to 5, the positive electrode paste 63P was prepared by varying the weight ratio of the solid content excluding the hydroxide particles 67 to the hydroxide particles 67. The lithium ion secondary batteries 1 of Examples 1 to 5 were otherwise prepared in the same manner.

[0039] Specifically, in Example 1, in the positive electrode paste preparation step, the mixing ratio of hydroxide particles 67 to the solid content of the solid content of positive electrode paste 63P excluding hydroxide particles 67 (hereinafter, this is also simply referred to as the mixing ratio of hydroxide particles 67) was 0.1 wt%. In Example 2, the mixing ratio of hydroxide particles 67 was 0.5 wt%. In Example 3, the mixing ratio of hydroxide particles 67 was 1.0 wt%. In Example 4, the mixing ratio of hydroxide particles 67 was 3.0 wt%. In Example 5, the mixing ratio of hydroxide particles 67 was 5.0 wt%.

[0040] <Comparative Example 1> In Comparative Example 1, in the positive electrode paste preparation step, the mixing ratio of hydroxide particles 67 to the solid content excluding hydroxide particles 67 in the solid content of positive electrode paste 63P was set to 0 wt %. That is, in Comparative Example 1, a positive electrode paste not including hydroxide particles 67 was prepared. Otherwise, the lithium ion secondary battery of Comparative Example 1 was prepared in the same manner as in Example 1.

[0041] <Investigation of the AlF3 coating on the positive electrode current collector foil> Next, the AlF3 coating on the surface of the positive electrode current collector foil was investigated for the lithium ion secondary batteries of Examples 1 to 5 and Comparative Example 1. All of the lithium ion secondary batteries investigated were lithium ion secondary batteries that were completed and ready for shipment, and were unused products (i.e., new products).

[0042] Specifically, each lithium ion secondary battery is disassembled to remove the positive electrode plate. The removed positive electrode plate is immersed in ethyl methyl carbonate for 10 minutes, and then dried to remove the components of the nonaqueous electrolyte 90 adhering to the positive electrode plate. Then, the positive electrode active material layer is peeled off from the positive electrode current collector foil 61 of the positive electrode plate to expose the first surface 61b and the second surface 61c of the positive electrode current collector foil 61. The first surface 61b and the second surface 61c of the positive electrode current collector foil 61 are analyzed by SEM-EDX (energy dispersive X-ray spectroscopy) to calculate the ratio of F element to Al element (F / Al). The results are shown in Table 1. The value of F / Al shown in Table 1 is the average value of the value of F / Al on the first surface 61b and the value of F / Al on the second surface 61c. It can be said that the greater the value of F / Al, the greater the amount of AlF 3 coating present on the first surface 61b and the second surface 61c of the positive electrode current collector foil 61.

[0043] [Table 1]

[0044] As shown in Table 1, the lithium ion secondary batteries of Examples 1 to 5 had larger F / Al values ​​than the lithium ion secondary battery of Comparative Example 1. From this result, it can be said that by producing a positive electrode plate 60 using the positive electrode paste 63P containing hydroxide particles 67 and manufacturing a lithium ion secondary battery 1 using this positive electrode plate 60, the formation of an AlF3 coating on the first surface 61b and the second surface 61c of the positive electrode current collector foil 61 is promoted, and the corrosion resistance of the first surface 61b and the second surface 61c of the positive electrode current collector foil 61 can be improved.

[0045] <High-load current test> Next, a high-load current test was conducted on the lithium-ion secondary batteries of Examples 1 to 5 and Comparative Example 1. Note that all of the lithium-ion secondary batteries used in this test were lithium-ion secondary batteries that were completed and ready for shipping, and were unused products (i.e., new products). Therefore, for all of the lithium-ion secondary batteries used in this test, the high-load current applied in this test was the high-load current applied in the early stages of use.

[0046] In this test, 20 charge / discharge cycles were performed for each lithium-ion secondary battery in a temperature environment of 25°C, with the following charge / discharge cycle being considered as one cycle. Specifically, the charge / discharge cycle was as follows: First, discharge at a current value of 0.2C until the battery voltage value reached 3.5V. Then, pause for 10 minutes. Then, charge at a current value of 1C until the battery voltage value reached 4.0V. Then, pause for 10 minutes. With this charge / discharge cycle as one cycle, 20 charge / discharge cycles were performed.

[0047] After performing the above-mentioned charge-discharge cycle for 20 cycles for each lithium ion secondary battery, the presence or absence of Al elution from the first surface 61b and the second surface 61c of the positive electrode current collector foil 61 was investigated. Specifically, after performing 20 cycles of charge-discharge cycles, each lithium ion secondary battery was disassembled to remove the positive electrode plate. Then, the removed positive electrode plate was immersed in ethyl methyl carbonate for 10 minutes, and then dried to remove the components of the nonaqueous electrolyte 90 attached to the positive electrode plate. Then, the positive electrode active material layer was peeled off from the positive electrode current collector foil 61 of this positive electrode plate to expose the first surface 61b and the second surface 61c of the positive electrode current collector foil 61. Then, the first surface 61b and the second surface 61c of the positive electrode current collector foil 61 were observed with a microscope to confirm the presence or absence of pitting corrosion. The pitting corrosion is due to the elution of Al from the first surface 61b and the second surface 61c of the positive electrode current collector foil 61. Therefore, the presence or absence of Al elution can be determined by the presence or absence of pitting corrosion. The results are shown in Table 1. In Table 1, "Al pitting corrosion" is recorded and rated on a three-level scale of ○, △, and ×.

[0048] As shown in Table 1, in Examples 2 to 5, the evaluation of Al pitting corrosion was ◯, and no pitting corrosion was present on the first surface 61b and the second surface 61c of the positive electrode current collector foil 61. From this result, it can be said that in the lithium ion secondary batteries 1 of Examples 2 to 5, when a high load current is applied in the early stage of use, it was possible to prevent Al elution from the first surface 61b and the second surface 61c of the positive electrode current collector foil 61. Therefore, it can be said that the lithium ion secondary batteries 1 of Examples 2 to 5 are lithium ion secondary batteries in which Al elution from the first surface 61b and the second surface 61c of the positive electrode current collector foil 61 is unlikely to occur when a high load current is applied in the early stage of use.

[0049] On the other hand, in Comparative Example 1, the evaluation of Al pitting corrosion was ×, and many pitting corrosions were present on the first surface 61b and the second surface 61c of the positive electrode current collector foil 61. Therefore, it can be said that the lithium ion secondary battery of Comparative Example 1 is a lithium ion secondary battery in which Al elution from the first surface 61b and the second surface 61c of the positive electrode current collector foil 61 is likely to occur when a high load current is applied in the early stage of use.

[0050] In Example 1, the evaluation of Al pitting was Δ, and pitting was present on the first surface 61b and the second surface 61c of the positive electrode current collector foil 61, but the number of pitting was small and the size was small compared to Comparative Example 1. From this result, it can be said that in the lithium ion secondary battery 1 of Example 1, when a high load current is applied in the early stage of use, the elution of Al from the first surface 61b and the second surface 61c of the positive electrode current collector foil 61 can be reduced compared to the lithium ion secondary battery of Comparative Example 1. Therefore, it can be said that the lithium ion secondary battery 1 of Example 1 is a lithium ion secondary battery in which elution of Al from the first surface 61b and the second surface 61c of the positive electrode current collector foil 61 is less likely to occur when a high load current is applied in the early stage of use, compared to the lithium ion secondary battery of Comparative Example 1.

[0051] From the above results, it can be said that by producing positive electrode plate 60 using positive electrode paste 63P containing hydroxide particles 67 and manufacturing lithium ion secondary battery 1 using this positive electrode plate 60, it is possible to manufacture a lithium ion secondary battery that can reduce "Al elution from the surface of the positive electrode current collector foil when a high load current is applied in the early stages of use." Therefore, it can be said that the manufacturing method of this embodiment is a manufacturing method of a lithium ion secondary battery that can reduce "Al elution from the surface of the positive electrode current collector foil when a high load current is applied in the early stages of use."

[0052] <Discharge capacity measurement test> Further, the discharge capacity was measured for the lithium ion secondary batteries of Examples 1 to 5 and Comparative Example 1. Specifically, first, each lithium ion secondary battery was charged at a current value of 0.2C until the battery voltage value reached 4.2V. Then, charging was performed while maintaining the battery voltage value at 4.2V, and SOC was set to 100%. Then, discharging was performed at a current value of 0.2C until the battery voltage value reached 3.0V. Then, discharging was performed while maintaining the battery voltage value at 3.0V, and SOC was set to 0%. At this time, the discharged amount of electricity from SOC 100% to SOC 0% was measured as the discharge capacity of each lithium ion secondary battery. Then, the magnitude of the discharge capacity of each lithium ion secondary battery was evaluated. The results are shown in Table 1.

[0053] As indicated by circles in Table 1, sufficient discharge capacity was obtained in the lithium ion secondary batteries of Examples 1 to 4 and Comparative Example 1. Specifically, the discharge capacity of the lithium ion secondary battery of Comparative Example 1 was the largest, and the discharge capacity of the lithium ion secondary battery manufactured with a higher mixing ratio (wt%) of hydroxide particles 67 (specifically, LiOH) was smaller. In particular, the discharge capacity of the lithium ion secondary batteries of Examples 1 to 4 was smaller than that of the lithium ion secondary battery of Comparative Example 1, but the amount of decrease was small.

[0054] On the other hand, as shown by △ marks in Table 1, the lithium ion secondary battery of Example 5 had a smaller discharge capacity than the lithium ion secondary battery of Comparative Example 1, and the amount of decrease was larger than those of the lithium ion secondary batteries of Examples 1 to 4. From this result, it was found that when the mixing ratio of hydroxide particles 67 (specifically, LiOH) was set to 5.0 wt % or more, the decrease in discharge capacity of the lithium ion secondary battery became large.

[0055] From the results of the high-load current test and the discharge capacity measurement test described above, it is more preferable that the mixing ratio of the hydroxide particles 67 is in the range of 0.5 wt% or more and less than 5.0 wt% in the positive electrode paste preparation process. Specifically, from the results of the high-load current test, it can be said that the effect of reducing Al elution from the positive electrode current collector foil 61 can be obtained by including the hydroxide particles 67 in the positive electrode paste 63P, but by setting the mixing ratio of the hydroxide particles 67 to 0.5 wt% or more, it is possible to reliably prevent Al elution from the positive electrode current collector foil 61. However, from the results of the discharge capacity measurement test, it was found that when the mixing ratio of the hydroxide particles 67 is 5.0 wt% or more, the decrease in the discharge capacity of the lithium ion secondary battery becomes large. Therefore, it can be said that it is more preferable that the mixing ratio of the hydroxide particles 67 is in the range of 0.5 wt% or more and less than 5.0 wt% in the positive electrode paste preparation process.

[0056] Although the present invention has been described above with reference to an embodiment, it goes without saying that the present invention is not limited to the above embodiment and can be modified as appropriate without departing from the spirit of the present invention.

[0057] For example, in the embodiment, an example in which LiOH particles are used as the hydroxide particles 67 is shown. However, even if other hydroxide particles are used, the formation of an AlF3 coating is promoted on the first surface 61b and the second surface 61c of the positive electrode current collector foil 61, and the corrosion resistance of the first surface 61b and the second surface 61c of the positive electrode current collector foil 61 can be improved. This can reduce "Al elution from the surface of the positive electrode current collector foil when a high load current is applied in the early stage of use." Specifically, even if hydroxide particles other than LiOH particles are used, the hydroxide particles decompose in the positive electrode active material layer to generate H2O. This causes the reactions of the above formulas 2 and 3, and an AlF3 coating is generated on the surface of the positive electrode current collector foil. [Explanation of symbols]

[0058] 1. Lithium-ion secondary battery 1B Filled battery 30 Battery case 50 Electrode body 60 Positive plate 61 Positive electrode current collector foil 63 Cathode active material layer 63P Positive paste 64 Positive electrode active material particles 65 Binder 66 Conductive materials 67 Hydroxide particles 69 Solvents 70 Negative plate 90 Nonaqueous electrolyte

Claims

[Claim 1] A positive electrode plate having a positive electrode active material layer on the surface of a positive electrode current collector foil made of aluminum foil, a negative electrode plate, and LiPF 6 and a battery case housing the nonaqueous electrolyte solution, a positive electrode paste preparation step of preparing a positive electrode paste by mixing positive electrode active material particles and a solvent; a positive electrode plate fabrication step of applying the positive electrode paste to the surface of the positive electrode current collector foil and drying the applied positive electrode paste to fabricate the positive electrode plate having the positive electrode active material layer on the surface of the positive electrode current collector foil; an electrode assembly fabrication step of fabricating an electrode assembly having the positive electrode plate and the negative electrode plate; a housing step of housing the electrode assembly inside the battery case; a liquid injection step of injecting the nonaqueous electrolyte into the battery case containing the electrode assembly to prepare a liquid injection-completed battery; and an initial charging step of initially charging the battery after the electrolyte injection is completed, In the positive electrode paste preparation step, the positive electrode paste is prepared by further mixing LiOH particles, and the mixing ratio of the LiOH particles to the solid content of the positive electrode paste excluding the LiOH particles is within a range of more than 2.0 wt % and less than 5.0 wt %. A method for manufacturing a lithium-ion secondary battery.

Citation Information

Patent Citations

  • Nonaqueous electrolyte secondary battery

    JP2001283849A

  • Nonaqueous electrolyte battery and positive electrode active material

    JP2006173049A

  • Nonaqueous electrolyte secondary battery

    JP2008021538A

  • Positive electrode for battery

    JP2014082050A

  • Method for manufacturing positive electrode active material layer for lithium ion battery, and positive electrode active material layer for lithium ion battery

    JP2016051610A